1963
DOI: 10.1063/1.1729526
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductivity and Time-Dependent Polarization in NaCl Crystals

Abstract: When a constant electric field is applied to a dielectric, the current density per unit field decreases with time from an ``initial conductivity'' to a ``final (or steady-state) conductivity.'' A study is made of this time-dependent polarization effect for ``pure'' NaCl crystals in the range from 50° to 200°C. The validity of Ohm's law and the superposition principle is demonstrated for these crystals; this establishes the linearity of the formal equation which relates polarization, electric field, and their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The final value of the current was recorded as recommended by Sutter. 19 The temperature of measurement was increased at a rate of 60 0 /h to the melting point of NaCl. The crystal temperature was determined to a precision better than ±0.5° by means of a calibrated Chromel Alumel thermocouple placed within 1 mm of the electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…The final value of the current was recorded as recommended by Sutter. 19 The temperature of measurement was increased at a rate of 60 0 /h to the melting point of NaCl. The crystal temperature was determined to a precision better than ±0.5° by means of a calibrated Chromel Alumel thermocouple placed within 1 mm of the electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…The present work shows that much low-temperature dc polarisation has little fundamental significance in terms of bulk crystal properties. This probably explains why, as has been previously observed [9], there is no general agreement on what causes time-dependent polarisation in alkali halides.…”
Section: Resultsmentioning
confidence: 70%
“…INTRODUCTION DURING recent years there has been an increasing realization that polarization effects due to blocking of ionic charge-carriers a t a dielectric-electrode interface can provide a mechanism for a.c. dielectric dispersion. Reviews have been given by Volger (1960) and Croitoru (1965) and several recent articles have given evidence of the existence of this type of mechanism in alkali halides (Allnatt and Jacobs 1961, Jacobs and Maycock 1963, Wintle and Rolfe 1966 and other ionic materials (Friauf 1954, Isard 1963, Sutton 1964. Similar effects have also been observed in thin film capacitors of NaCl and NaBr with silver electrodes (Macfarlane and Weaver 1966).…”
mentioning
confidence: 76%
“…On the other hand, some authors claim to have demonstrated that electrode polarization effects are not generally observable in alkali halide specimens (Hamon 1953, Sutter andNowick 1963). The latter, in particular, made a careful study of d.c. polarization effects in pure NaCl crystals and found no evidence of electrode polarization except in cases where poor electrode cont)act with the crystal was deliberately introduced.…”
mentioning
confidence: 99%
See 1 more Smart Citation